2008
DOI: 10.1124/jpet.107.136044
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C75-Involved Autoinduction of Metabolism in Rhesus Monkeys of Methyl 3-Chloro-3′-fluoro-4′-{(1R)-1-[({1-[(trifluoroacetyl)amino]cyclopropyl}carbonyl)amino]ethyl}-1,1′-biphenyl-2-carboxylate (MK-0686), a Bradykinin B1 Receptor Antagonist

Abstract: After oral treatment (once daily) for 4 weeks with the potent bradykinin B 1 receptor antagonist methyl 3-chloro-3Ј-fluoro-4Ј-{(1R)-1-[({1-[(trifluoroacetyl)amino]cyclopropyl}carbonyl)-amino]ethyl}-1,1Ј-biphenyl-2-carboxylate (MK-0686), rhesus monkeys (Macaca mulatta) exhibited significantly reduced systemic exposure of the compound in a dose-dependent manner, suggesting an occurrence of autoinduction of MK-0686 metabolism. This possibility is supported by two observations. 1) MK-0686 was primarily eliminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The following case investigated in our lab (65) exemplifies the divergent outcome of auto-induction in rhesus monkeys and humans, and the mechanic investigation of the event. A potent bradykinin B 1 receptor antagonist was primarily eliminated via biotransformation in rhesus monkeys, with oxidation on the chlorophenyl ring as one of the major metabolic pathways.…”
Section: Cyp3a-mediated Ddis In Monkeysmentioning
confidence: 97%
“…The following case investigated in our lab (65) exemplifies the divergent outcome of auto-induction in rhesus monkeys and humans, and the mechanic investigation of the event. A potent bradykinin B 1 receptor antagonist was primarily eliminated via biotransformation in rhesus monkeys, with oxidation on the chlorophenyl ring as one of the major metabolic pathways.…”
Section: Cyp3a-mediated Ddis In Monkeysmentioning
confidence: 97%
“…Of these, African green monkey CYP2C9 has been characterized. African green monkey CYP2C9 is involved in diclofenac 4′ -and 5-hydroxylation (Table 3), but much less than either human CYP2C9 or rhesus CYP2C19 (Tang et al, 2008). Marmoset CYP2C8 cDNA is 93% identical to human CYP2C8 cDNA (Table 2), and its protein metabolizes tolbutamide (Table 3), but not diclofenac, S-mephenytoin, or paclitaxel (Narimatsu et al, 2006).…”
Section: Cyp2c Subfamilymentioning
confidence: 97%
“…Human PK data from MK-0686 are available. 391 Interestingly, it has recently been reported that B 1 receptor antagonists, such as LF22-0542 (44), a water-soluble arylsulfonamide are promising candidates for treating diabetic retinopathy after ocular application. 392 Common binding motifs of aryl sulfonamides and biarylmethyl amines have been proposed 393 and all data from structureactivity relationship and homology modeling 394,395 should hopefully promote the discovery of investigational drugs antagonizing the B 1 receptor and that are successful in clinical use.…”
Section: Drug-like Bradykinin Receptor Antagonists and Agonistsmentioning
confidence: 99%